Research on map-positioning technology based on W3C Geolocation API - Changrong Xu; Feilun Chen (2012 2nd International Conference on Consumer Electronics, Communications and Networks, 2012)
It is a severe situation for the traditional Geolocation web applications to collect GIS data based on user IP addresses, WiFi APs, GSM&CDMA stations or GPS in a sustained and stable way. Meanwhile, the GIS data acquired in the traditional way must be transformed to coordinates to locate the client's position based on client-side Java-scripts analysis, and that needs connecting to exclusive database to query user's location information, which requires certain professional knowledge of GIS for developers. The Geolocation API is an interface used to perceive geo-spatial location of the client device designed by W3C and can easily seamlessly archive web client's location integrated with HTML5. This paper researches the key technologies of how to get the map positioning of WebGIS using W3C Geolocation APIs based on HTML5 specification, and it has been implemented a distribution and aggregation model of social network members.